Pelaksanaan Pendaftaran Hak Tanggungan yang Terintegrasi Secara Elektronik di Kabupaten Agam - Satria, Angga; Yakub, Yulizar; Syuryani, Syuryani (Universitas Ekasakti, 2023)
Based on Article 1 paragraph (1) of the UUHT, Mortgage Rights on land and objects related to land are security rights that are imposed on land rights as referred to in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, along with or without other objects that are an integral part of the land, for the repayment of certain debts, which give priority to certain creditors against other creditors. Mortgage rights begin with a debt and credit agreement entered into by the debtor and his creditor. This is followed by the making of a deed of granting mortgage rights (APHT) made by a Land Deed Official (PPAT). Before 2020, APHT registration was carried out by PPAT at the Land Office directly or manually. This is different after 2020, APHT registration is carried out online or electronically, with the enactment of Regulation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency Number 5 of 2020 concerning Electronically Integrated Mortgage Services. In its implementation after the enactment of the aforementioned regulation, there are several problems in the Implementation of Electronic Registration of Deeds of Granting Mortgage in Agam Regency. With problems: 1) How is the implementation of electronically integrated Mortgage Rights registration in Agam Regency? 2) How are the obstacles and constraints to electronically integrated registration of mortgage rights in Agam Regency? This research uses an empirical juridical approach and the nature of the research is descriptive. The implementation of Electronic Registration of Deeds of Mortgage in Agam Regency has been running well and in accordance with applicable regulations and has fulfilled the principles of electronic registration of mortgage rights, namely fast, precise and easy. Meanwhile, there are still obstacles both at the land office, PPAT and banks. One of them is that there are still many land data that have not been validated and the lack of human resources at the land office. Meanwhile, in PPAT and banking, there are still errors in typing APHT and its application.